Penerapan Standar Akuntansi Pemerintahan Dalam Mempertanggungjawabkan Keuangan Desa Padang Mahondang Kecamatan Pulau Rakyat Kabupaten Asahan (Jurnal Kendali Akuntansi, 2023)
This study aims to find out whether Padang Mahondang Village has implemented Government Accounting Standards in its Village Financial Accountability in accordance with PSAP No.01, to find out what procedures are made by Padang Mahondang Village in Presenting Village Financial Accountability Reports and What are the obstacles experienced by the village in the Implementation of Government Accounting Standards in Village Financial Accountability in accordance with PSAP No.01. The research methodology used is qualitative research. The data sources used are primary data obtained by direct interviews and secondary data obtained from related documents. The location of this research is in Padang Mahondang Village, Pulau Rakyat District, Asahan Regency. The results of this study can be concluded that the Application of Government Accounting Standards in Village Financial Accountability in this village has not been fully said to be good because there are still several financial reports that have not been made by the village government and the procedure for preparing village financial accountability reports is appropriate whereby making an Accountability Report Realization of APBDes Implementation, Village Regulations, Village-Owned Wealth Reports and Government and Regional Government Program Reports that enter the village.